Novada iedzīvotāju līdzestība mutes dobuma veselības profilaksē - Ozola, Agnija (Latvijas Universitāte, 2014)
Agnijas Ozolas bakalaura darbs „Novada iedzīvotāju līdzestība mutes dobuma veselības profilaksē”, 2014.gads. Pētījums veikts vienā novadā, ārstniecības iestādē – pacientu un darbinieku vidū. Pētniecības darbā analizēta literatūra par mutes dobumu, mutes dobuma biežākajām saslimšanām un ikdienas mutes dobuma higiēnu. Darba mērķis: izzināt iedzīvotāju līdzestību mutes dobuma veselības profilaksē. Hipotēze: iedzīvotāju līdzestība mutes dobuma veselības profilaksē ir nepietiekama. Metode: kvantitatīvā pētniecības metode, instruments: anketa. Pētījumā piedalījās 100 respondenti, vecumā no 18 – 65 gadiem (61 sieviete un 39 vīrieši). Pētījums izvirzīto hipotēzi atbalsta, novada iedzīvotāju līdzestība mutes dobuma veselības profilaksē ir nepietiekama. Atslēgvārdi: mutes dobums, higiēna, līdzestība, veselība, profilakse.

The diploma paper of Agnija Ozola “Cooperation of district’s inhabitants in prevention of mouth hollow health”, year 2014. The research was carried out in one specific district, in medical institution among patients and medical employees. During the research the literature about mouth’s hollow, constant illnesses of mouth’s hollow and daily care about mouth’s hygiene was analysed. The aim of the research paper: to inquire about inhabitants’ cooperation in prevention of mouth’s hollow health. The hypothesis of the research: Inhabitants’ cooperation in prevention of mouth’s hollow health is insufficient. The method of the research: quantitative research method. The instrument of the research: questionnaire. 100 respondents at the age of 18 to 65 years were surveyed for the research. (61 women and 39 men). The research proves the hypothesis that district’s inhabitants’ cooperation in prevention of mouth’s hollow health is insufficient. Keywords: mouth hollow, hygiene, cooperation, health, prevention.
Region population`s participation in health`s prevention of the mounth`s cavity
Keywords: Medicīna